Audio-visual resources and learning improvement: an experimental analysis - Magadán Díaz, Marta; Rivas García, Jesús Israel (International Journal of Learning Technology, 2023)
The general objective of this research is to analyse the students’ learning performance on the use of audio-visual resources in the subject of didactics of the business and its environment, taught in master’s degree in Teacher Training of High School, Vocational Training and Language Teaching (specialty in Economics, Business, and Commerce) at the University of Nebrija. This study applied the experimental method from two randomly generated samples of the two groups (virtual classrooms) into which the enrolled students were administratively divided. The results obtained by the experiment point to a significant improvement in the students’ learning performance, and their perception about the use of this didactic tool turned out to be very positive.
Keywords: audio-visual resources; digital teaching resources; experimental analysis; experimental method; learning; learning improvement; virtual classrooms; multimedia teaching; videos in class; audio-visual didactics; Emerging; Scopus